Surgery for the obese - Amjad, Nasser Muhammad (The College of Surgeons of Sri Lanka, 2014)
This review focuses on the problem of obesity from an asian perspective and the current evidence that supports the benefits of Bariatric surgery over conventional treatment for sustained weight loss. The requirements for an effective Bariatric surgical service are highlighted. Principles of peri-operative management and the currently practiced operative procedures are discussed briefly. Finally a short evaluation of the benefits and complication of the different procedures are presented.